Performance Enhancement of a Squashed Mender Antenna for Wireless Sensor Network Applications Operating in ISM Band - Sudhir Akojwar, Harish Rajurkar (International Journal of Advanced Science and Technology, 2019)
Immense achievements have been reached in antenna engineering since the pioneer work of Hertz and Marconi in demonstrating the existence of radio waves. An uninterrupted development and state of art designs of patch antennas leads a significant enhancement in the performance of wireless sensor network (WSN). The deployment of patch antenna in WSN significantly reduces the size of the sensor node and provided better impedance matching and hence better power transfer. With a patch antenna by means of optimized geometry and matching structure, a size optimization and better power transfer is possible in WSN. In this paper a very basic traditional shape of mender antenna is considered which on modification results in better return loss and size reduction in comparison with some existing work. The proposed work presents a low profiles & better return loss mender antenna designs operating on 2.4GHz, ISM band with fabrication results proposing that the projected designs contribute for performance improvement of WSN and provides good impedance matching. Keywords: Wireless Sensor Network, patch antenna, mender antenna, return loss, VSWR